Analisis Usability Commuter Line Vending Machine (C-VIM) - Maria Magdalena Wahyuni Inderawati; Ronald Sukwadi; Maria Cicilia Gunshleina (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2025)
To improve the quality of its services, PT. KRL Commuter Line has implemented various innovations to enhance the commuter line experience. One such innovation is the introduction of ticket vending machines, known as Commuter Line Vending Machines (C-VIM), for ticket purchase transactions. Implementing a new system often encounters various challenges that hinder its smooth operation, including the C-VIM implementation. Therefore, this study aims to determine the usability level of C-VIM. The analysis is based on usability dimensions, which include efficiency, error, learnability, memorability, and satisfaction. The methods are using performance measurement techniques, retrospective think-aloud (RTA), the System Usability Scale (SUS) questionnaire, and the Questionnaire for User Interaction Satisfaction (QUIS). A minimum sample of 40 subjects was allocated to each category. Ascertaining the population size is not feasible, considering the volatile daily passenger count. The usability score based on the SUS questionnaire was 66,43. Testing the efficiency dimension revealed that C-VIM does not yet have a high level of efficiency. However, in terms of error, learnability, and memorability, the system performed well. Regarding satisfaction, the QUIS score obtained was 60.99, indicating that customer satisfaction is fairly satisfactory. The proposed remediation process involves rearranging the physical layout of the screen, the placement of tickets, cash receptacles, and several other attributes. Furthermore, improvements are required for the on-screen display of several pages which were assessed to have low usability based on respondent feedback following the usability measurement.